Effect of aluminum on the non-enzymatic oxidation of dopamine. - Marinho, C R; Manso, C F (Acta Médica Portuguesa, 1994)
The effect of different concentrations of aluminum sulphate on the nonenzymatic oxidation of dopamine was studied in order to evaluate the action of this metal on neuromelanin synthesis. Data shows that under the studied conditions, aluminum partially inhibits dopamine self-oxidation, decreasing the formation of some intermediate compounds, namely dopaminequinone and dopaminochrome. If neuromelanins have a cytoprotective function in the central nervous system, possibly acting as intracellular scavengers of free radicals and redox metal ions, their decrease due to aluminum could be responsible for serious damage to neuronal tissues.